The Positive Relationship Between the Low-Density Lipoprotein Cholesterol/Apoprotein B Ratio and Bone Turnover Markers in Patients With Type 2 Diabetes - Lu, Chun-feng; Liu, Wang-shu; Huang, Hai-yan; Ge, Xiao-qin; Hua, Ling-yan; Wang, Xue-qin; Su, Jian-bin (Frontiers in Endocrinology, 2022)
Background: Dyslipidemia may contribute to low bone turnover in patients with type 2 diabetes (T2D) through mediating oxidative stress and atherosclerosis. The low-density lipoprotein cholesterol/apoprotein B (LDL-C/Apo B) ratio is a surrogate marker of small and density low-density lipoprotein cholesterol (sd-LDL-C), a most harmful group of LDL-Cs. The present study aimed to investigate the association between the LDL-C/Apo B ratio and bone turnover in patients with T2D. Methods: This study was a cross-sectional study enrolled patients with T2D from January 2021 to December 2021. Each participant was assessed for lipid profiles, bone turnover markers (BTMs), lumbar spine (L1-L4) and hip dual-energy X-ray absorptiometry (DXA) scans. Osteoporosis was diagnosed as a T-score lower than or equal to -2.5 at the spine or hip. Results: A total of 335 patients with T2D were enrolled in the study, and the LDL-C/Apo B ratio ranged from 0.78 to 4.00. Along with the LDL-C/Apo B ratio tertile ascending, osteocalcin (OC), C-terminal telopeptide (CTx) and N-terminal propeptide of type-I procollagen (PINP) levels gradually increased (all p < 0.05). There were no differences in lumbar spine and hip T-score, proportion of osteoporosis (all p > 0.05) among the three subgroups. The LDL-C/Apo B ratio was positively correlated with lnOC (r = 0.244, p < 0.001), lnCTx (r = 0.226, p < 0.01) and lnPINP (r = 0.211, p < 0.001). These significant positive correlations persisted even when divided into male and female subgroups. Furthermore, three multiple linear regression analyses were constructed to investigate the independent association of the LDL-C/Apo B ratio with the BTMs levels. After adjusting for other clinical parameters, the LDL-C/Apo B ratio was still significantly associated with OC level (β = 0.199, t = 3.348, p < 0.01), CTx level (β = 0.238, t = 4.084, p < 0.001) and PINP level (β = 0.162, t = 2.741, p < 0.01). Conclusion: The LDL-C/Apo B ratio was significantly and positively associated with BTMs in patients with T2D. In clinical practice, more attention should be paid to the patients with T2D whose LDL-C/Apo B ratio is relatively low for the purpose of maintaining bone health.